Buzzing with questions : the inquisitive mind of Charles Henry Turner - Harrington, Janice N. (Calkins Creek an imprint of Highlights, 2019)
Questions buzzed endlessly in Charles Henry Turner's mind. Fascinated by bugs and other animals, he wondered: Can spiders learn? How do ants find their way home? Can bugs see color? --from dust jacket.